Simultaneous separation of triterpenoid saponins and flavonoid glycosides from the roots of Glycyrrhiza uralensis Fisch by pH‐zone‐refining counter‐current chromatography. Issue 19 (21st August 2013) - Xu, Jinfang; Luo, Jianguang; Kong, Lingyi
<x xml:space="preserve">Abstract</x> Glycosides including triterpenoid saponins and flavonoid glycosides are the main constituents of Glycyrrhiza uralensis Fisch (licorice) and exhibit prominent pharmacological activities. However, conventional methods for the separation of glycosides always cause irreversible adsorption and unavoidable loss of sample due to their high hydrophilicities. The present paper describes a convenient method for the simultaneous separation of triterpenoid saponins and flavonoid glycosides from licorice by pH‐zone‐refining counter‐current chromatography. Ethyl acetate/n‐butanol/water (2:3:5, v/v) with 10 mM TFA in the upper organic stationary phase and 10 mM ammonia in the lower aqueous mobile phase was used as the biphasic solvent system. Three triterpenoid saponins and two flavonoid glycosides including licorice‐saponin A3 (63.3 mg), glycyrrhizic acid (342.2 mg), 3‐O‐[β‐d‐glucuronopyranosyl‐(1 → 2)‐β‐d‐galactopyranosyl]glycyrrhetic acid (56.0 mg), liquiritin apioside (232.6 mg), and liquiritin (386.5 mg) were successfully obtained from licorice ethanol extract (2 g) in one step. This method subtly takes advantage of the common acidic properties of triterpenoid saponins and flavonoid glycosides, and obviously is much more efficient and convenient than the previous methods. It is also the first time that the separation of acidic triterpenoid saponins by using pH‐zone‐refining counter‐current chromatography has been reported.